The Influence Of Customer Satisfaction And Service Quality Towards Customer Loyalty In Pt. Mitra Andalan Trans Anugerah - Mudayat Mudayat (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose:. The formulation of the problem in this study is how the relationship between customer satisfaction and service quality to customer loyalty at PT. Trans Anugerah Mainstay Partners. The study population was all expeditionary service users, while the sample taken was 45 respondents. Before the data were analyzed, the data quality was tested using validity and reliability tests. Design/methodology/approach: This research is a quantitative method and data analysis techniques with a multiple linear regression. Findings: The results showed that the questionnaire items were valid and all variables were reliable. Based on the results of the analysis and discussion, it can be concluded that the variable Customer Satisfaction (X1) has a significant relationship with Customer Loyalty (Y), meaning that if the customer is satisfied, it will increase Customer Loyalty. Service Quality Variable (X2) has a significant relationship with Customer Loyalty (Y) This means that if the quality of service provided is good, then customer loyalty will increase. Customer satisfaction and service quality have a significant effect together on customer loyalty, meaning that if customer satisfaction and service quality are better, it will increase customer loyalty. The variable that has the most dominant influence is customer satisfaction with a beta value of 0.608. Paper type: Research paper